Navigating the Infodemic: Assessment and comparison of awareness and usage of magnifying loupes among Dental Students and Dental Practitioners – A Cross-Sectional Study - Khond, Mugdha; Vyavahare, Supriya; Yadav, Sakshi; Tivrekar, Siddhi; Mudaliyar , Sowmiya; Munankar, Anushka (Journal of Neonatal Surgery, 2025)
N\A